Reconstruction of Complex Lateral Skull Base Defects After Oral Cancer Resection With Individualized Anterolateral Thigh Flap - Gong, Zhaojian; Zhang, Shanshan; Chen, Chang; Zhi, Yuan; Zi, Moxin (Frontiers in Oncology, 2021)
Objectives Complex lateral skull base defects resulting from advanced or recurrent oral cancer resection are continuously challenging reconstructive surgeons. This study aimed to use reconstructive methods for lateral skull base defects, explore their feasibility, and evaluate the efficacy of defect reconstruction using anterolateral thigh (ALT) flaps. Patients and Methods We performed a retrospective case series of 37 patients who underwent lateral skull base defect reconstruction using the ALT/anteromedial thigh (AMT) flap between March 2016 and May 2021 at the Second Xiangya Hospital. The design and harvest of the flaps, methods for defect reconstruction, and reconstructive efficacy are described. Results Of the 37 patients, 3 were women and 34 were men, with a mean age of 51.7 years. Among the defects, 26 were through-and-through defects and were reconstructed using ALT chimeric flaps, double ALT flaps, folded ALT flap, combined ALT chimeric flaps and AMT flaps, or combined ALT chimeric flaps and pectoralis major flaps; the large lateral skull base dead spaces were filled with muscle tissues or fatty tissues. Postoperatively, 38 of the 39 ALT/AMT flaps survived completely, and the remaining flap experienced partial necrosis. Venous compromise occurred in one patient who was salvaged after operative exploration. Oral and maxillofacial wound infections occurred in two patients, salivary fistula in three patients, and thigh wound effusion in three patients. The wounds healed gradually in all patients after repeated dressing changes. Thirty-three patients were followed up for approximately 3–60 months; their oral functions and appearance were acceptable, and thigh motor dysfunction was not observed. Conclusions With the convenient flap design and muscle flap harvest, large and individualized tissue supply, feasible combination with other flaps, effective reduction or avoidance of wound complications, and acceptable donor site morbidity, the ALT flap is an appropriate choice for complex lateral skull base defect reconstruction.